Protein Adhesion on Atmospheric Plasma Deposited Quaternary Ammonium Salt Coatings. Issue 6 (19th March 2013) - Donegan, Mick; Dowling, Denis P.
Abstract This study investigates protein adhesion on nm thick helium atmospheric plasma deposited quaternary ammonium salt (QAS) coatings. The adhesion of the proteins BSA, IgG and Fg was evaluated on coated and uncoated silicon wafer substrates. This study was carried out in PBS solution, under flow conditions using ellipsometry. The QAS was found to exhibit a low level of solubility in PBS over time (approx. 2 nm h−1). On addition of both the IgG and Fg proteins, it was found that a protective protein layer of 7 and 2 nm respectively was formed, which prevented further dissolution of the QAS. In contrast the 1 nm thick BSA protein layer, which formed on the QAS, was insufficiently thick to prevent the slow dissolution of the salt. It was concluded that the charge and structure of the protein influences its adhesion on the QAS surface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>